Implementasi Deep Learning: Suatu Inovasi Pendidikan - Sari, Ambar Wulan; Arta, Dewi Juni (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
The development of artificial intelligence technology has presented great opportunities intransforming education, one of which is through the deep learning approach. This article aims to describethe implementation of deep learning as an innovation in learning that emphasizes conceptual understanding,active involvement, and the development of critical thinking skills. The research method used is a literaturestudy with a qualitative descriptive approach. The results of the study show that deep learning can beimplemented through models such as project-based learning, inquiry learning, and role-playing, which arein line with the principles of the Independent Curriculum. However, its implementation still faces challengessuch as limited digital literacy of teachers, uneven infrastructure, and the need for supporting training andpolicies. This study concludes that deep learning has great potential in improving the quality of learning thatis adaptive to the digital era, as long as it is supported by a conducive education ecosystem..Keywords: Deep learning, educational innovation, Independent Curriculum, learning technology, 21stcentury skills.